Preface: SI on Engineering Optimization - Błachowski, Bartłomiej; Tauzowski, Piotr (Computer Assisted Methods in Engineering and Science, 2020)
This issue of CAMES is dedicated to the memory of Professor Witold Gutkowski in recognition of his vision, leadership, and contributions to the field of Structural Optimization. The contents of this special issue comprise a biography of Professor Gutkowski and six research papers presented during the Workshop on Engineering Optimization (WEO-2019). The Workshop was held at the Institute of Fundamental Technological Research of the Polish Academy of Sciences (IPPT PAN) on November 4th, 2019, and gathered 30 participants from five European countries. The papers address a variety of applications and  cover a breadth of topics ranging from theory to computational methods. Engineering Optimization is a multidisciplinary research area applied in such fields as: mechanical, aeronautical, electrical and civil engineering. In particular, since its beginning in the nineteenth century and the pioneering works by Maxwell and Michell, significant progress in structural optimization has been made. Initially in the field of structural optimization researchers worked on size and shape optimization problems. Currently, their efforts are oriented towards topology optimization under deterministic or probabilistic forces with multiple load conditions and the designs based on linearly elastic or elastoplastic materials.